568. The Impact of Disclosure Stigma on Virologic Outcomes in People Living with HIV. (26th November 2018) - Matheu, Michelle; Gleason, Laurie; Sunil, Thankam; Castro-Pena, Norys A; Spears, Camille; Smith, Christopher; Flores, John Michael; Taylor, Barbara S
Abstract: Background: HIV-related stigma is a leading barrier to engagement in HIV care and successful treatment. Disclosure Stigma (DS), the fear of disclosing one's serostatus, is associated with poor adherence and retention in care, but its association with clinical indicators of HIV treatment is not well established. The purpose of this study was to determine the influence of DS on virologic suppression, and our hypothesis was that DS would be associated with lack of virologic suppression. Methods: This cross-sectional study was performed between May 2015 and February 2016, at the largest publicly funded HIV clinic in South Texas. A survey was administered to consecutively recruited participants at routine follow-up who were: ≥18-years-old, HIV+, and receiving antiretroviral therapy. Surveys included demographics, sexual/HIV history, AIDS Clinical Trials Group baseline adherence questionnaire, and a validated HIV-stigma scale. Clinical data were obtained from medical records. The primary predictor was DS: the sum of 10 items ranked 0–4, with maximum score of 30 indicating highest stigma. The primary outcome was lack of virologic suppression (LOVS): most recent HIV-1 RNA>20 copies/mL. Bivariate analyses were conducted to examine: (i) predictors of DS and (ii) predictors of LOVS. Multivariate logistic regression models examined the relationship between DS and LOVS. Results: For 275 participants, median DS score was 18.5 (IQR 13, 23). In bivariate analysis, depression (OR 1.10; CI 1.05, 1.15) and perceived stress (OR 1.04; CI 1.01, 1.08) were significantly associated with increased DS. However, dissatisfaction with help received by friends/family was associated with reduced odds of DS (OR 0.46; CI 0.27, 0.78). DS was significantly inversely associated with LOVS (OR 0.96; CI 0.92, 0.99) and age (OR 0.97; CI 0.95, 0.998), and positively associated with drug use (OR 3.96; CI 1.53, 10.23). The association between DS and LOVS was maintained after adjusting for age, gender/sexual orientation, race/ethnicity, and drug use. Conclusion: DS was highly prevalent in this cohort. The unanticipated inverse association between DS and LOVS highlights the complexity of this relationship. Despite this association, the balance of data in this cohort demonstrates an overall negative impact of DS. Further study is needed to understand this surprising finding. Disclosures: All authors: No reported disclosures.